Bankruptcy Prediction Analysis on PT Blue Bird Tbk - Aulia; Hendra Saputra; Eva Nanda Wulandari (International Journal of Management, Economic and Accounting, 2024)
This research is a quantitative descriptive study that aims to determine how the Springate Method, Zmijewski Method, and Grover Method analyze bankruptcy at PT Blue Bird Tbk with the period used in this study is six years, starting from 2016-2021. This research was conducted by taking secondary data in the form of financial reports obtained from the official website www.bluebirdgroup.com. The Springate method used to analyze the bankruptcy condition of PT Blue Bird Tbk in the 2016-2021 period, there were two years in the vulnerable area, namely 2016 and 2018, in 2017 the company was in a healthy condition or not bankrupt. The Zmijewski method used to analyze the bankruptcy condition of PT Blue Bird Tbk in the 2016-2021 period, that the six consecutive years did not experience bankruptcy. The Grover method used to analyze the bankruptcy condition of PT Blue Bird Tbk in the 2016-2021 period, that the six consecutive years did not experience bankruptcy.PT Blue Bird Tbk was in a vulnerable area in 2016 and 2018, but for 2017 the company was in a healthy condition or not bankrupt. While experiencing bankruptcy in 2019-2021 using the Springate method and this method is accurate in analyzing bankruptcy in this company. While the Zmijewski and Grover in the six years 2016-2021, PT Blue Bird Tbk is in a healthy condition or not bankrupt.